IMPLEMENTASI PELAKSANAAN PENDIDIKAN INKLUSI DI SD BINA HARAPAN SEMARANG - Eka Sari Setianingsih; Ikha Listyarini (Universitas Sarjanawiyata Tamansiswa, 2019)
The implementation of inclusive education enables children with special needs to learn together with the normal students in regular schools. The study aimed to analyze the implementation of inclusive education at Bina Harapan Semarang Elementary School. The method in this study was descriptive qualitative analysis. Subjects were students, teachers, and employees/staff. Data collection techniques used were interviews, observation, and documentation. To check the validity of the data, the researcher used data triangulation techniques. The results showed that the implementation of inclusive education at Bina Harapan Semarang Elementary School was not by the provisions. It was due to the absence of a decree on the appointment of the implementation of inclusive education so that the fulfillment of various supporting components for the implementation of inclusive education had not been fully fulfilled. And it was also found that school license was to administer the inclusive education, but in fact the curriculum used was a regular curriculum, all students in schools were dominated by children with special needs, teachers did not have special education skills, there were no common perceptions about children with special needs, teachers were still not considered sensitive and proactive yet to the special needs of children. Suggestions are needed to evaluate school licensing and implementation of school administration, human resources in teaching, acceptance of new students, and awareness of all parties to be actively involved in various activities to support the implementation of inclusive education.The implementation of inclusive education enables children with special needs to learn together with the normal students in regular schools. The study aimed to analyze the implementation of inclusive education at Bina Harapan Semarang Elementary School. The method in this study was descriptive qualitative analysis. Subjects were students, teachers, and employees/staff. Data collection techniques used were interviews, observation, and documentation. To check the validity of the data, the researcher used data triangulation techniques. The results showed that the implementation of inclusive education at Bina Harapan Semarang Elementary School was not by the provisions. It was due to the absence of a decree on the appointment of the implementation of inclusive education so that the fulfillment of various supporting components for the implementation of inclusive education had not been fully fulfilled. And it was also found that school license was to administer the inclusive education, but in fact the curriculum used was a regular curriculum, all students in schools were dominated by children with special needs, teachers did not have special education skills, there were no common perceptions about children with special needs, teachers were still not considered sensitive and proactive yet to the special needs of children. Suggestions are needed to evaluate school licensing and implementation of school administration, human resources in teaching, acceptance of new students, and awareness of all parties to be actively involved in various activities to support the implementation of inclusive education.